Batas ng lansangan ([Quezon City] Regal Films Production)
Army major Ruben Medrano (Fernando Poe Jr.) was once part of an elite anti-kidnapping task force. An unfortunate incident during an operation got him suspended and sent back to Manila. There he tries to renew ties with his daughter Marissa (Kaye Abad) who has been living with his dead wife's sister Mariel (Dina Bonnevie). Marissa refuses to recognize her father because of all his shortcomings in the past. Nevertheless, Ruben decided to do something about them.
VCD
Executive producer Eric M. Cuatico ; directed by Ronwaldo Reyes
Fernando Poe, Jr. , Dina Bonnevie, Roi Vinzon, Kaye Abad
Keywords: Feature films ; Drama ; Comedy